Development of a fault-tolerant bus system suitable for a high-performance, embedded, real-time application on SUNSAT's ADCS - Farr, Xandri C. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MEng)--University of Stellenbosch, 2000.